Among the Titans. Tondo by Vyacheslav Mikhailov - Staniukovich-Denisova, Ekaterina Yu. (Actual Problems of Theory and History of Art, 2016)
The report discusses the Renaissance allusions in the painting of the St. Petersburg artist Vyacheslav Mikhailov. His picture “Tondo. Piazza di Spagna” (2002) was chosen as the emblem of the international conference “Actual problems of theory and history of art” in 2015.
Keywords: Vyacheslav Mikhailov; St. Petersburg artists; Renaissance motifs; traditions; tondo